The future of the past : a conservation ethic for architecture, urbanism, and historic preservation - Semes, Steven W. (New York : W.W. Norton & Company, Inc., 2009)
A comprehensive and eloquent argument for (3z(Bnew traditional(3y (Barchitecture that preserves the style and character of historic buildings. With contemporary design being redefined by architects and urbanists who are recovering the historic language associated with traditional architecture and the city, how might preservation change its focus or update its mission? Steven W. Semes, winner of the 2010 Clem Labine Award, makes a persuasive case that context matters and that new buildings and additions to old buildings should be harmonious with their neighbors. The Future of the Past was also named one of Planetizen's most noteworthy books of 2010 and one of The Atlantic Cities' "10 Most Compelling Historic Preservation Reads."s
Acknowledgments -- 1. New and old architecture together -- 2. The principles of traditional architecture -- 3. How traditional architecture works -- 4. The modernist paradigm -- 5. A brief history of preservation philosophy -- 6. Historicism and the search for an architecture of our time -- 7. Preservation after historicism -- 8. Literal replication -- 9. Invention within a style -- 10. Abstract reference -- 11. Intentional opposition -- 12. A conservation ethic -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: ARCHITECTURE AND HISTORY